Incorporating Serum Level of Hepatitis B Surface Antigen or Omitting Level of Hepatitis B Virus DNA Does not Affect Calculation of Risk for Hepatocellular Carcinoma in Patients Without Cirrhosis - Yang, Hwai-I; Tseng, Tai-Chung; Liu, Jessica; Lee, Mei-Hsuan; Liu, Chun-Jen; Su, Tung-Hung; Batrla-Utermann, Richard; Chan, Henry Lik-Yuen; Kao, Jia-Horng; Chen, Chien-Jen (Clinical gastroenterology and hepatology, 2016)
Tests for hepatitis B virus (HBV) DNA are expensive, and levels of hepatitis B surface antigen (HBsAg) can help determine the risk for hepatocellular carcinoma (HCC) in patients with chronic HBV infection. We investigated how adding data to knowing the level of HBsAg or excluding measurement of HBV DNA affected the accuracy of the Risk Estimation for Hepatocellular Carcinoma in Chronic Hepatitis B (REACH-B) scoring system in determining the risk for HCC. We collected data from 3584 patients with chronic HBV infection who were positive for HBsAg, free of cirrhosis, and participated in the community-based Risk Evaluation of Viral Load Elevation and Associated Liver Disease/Cancer (REVEAL)-HBV cohort (208 cases of HCC) from 1991 through 1992; they were followed up until December 31, 2008. Data from this cohort were used to derive our scoring system. We validated our system using data from 2688 HBsAg-seropositive patients (191 cases of HCC) who participated in the hospital-based Elucidation of Risk Factors for Disease Control or Advancement in Taiwanese Hepatitis B Carriers (ERADICATE-B) study at the National Taiwan University Hospital from 1985 through 2000; they were followed up until December 31, 2010. We also validated the system using data from 426 patients with chronic HBV infection who participated in the Chinese University of Hong Kong (CUHK) study (46 cases of HCC) from 1997 through 2000; patients were followed up for a median of 225 weeks. Discrimination and calibration were evaluated using area under the receiver operating characteristic (AUROC) curves and calibration charts. When data on HBsAg were added to the REACH-B scoring system, it identified patients in the ERADICATE-B study who developed HCC within 3, 5, and 10 years, with AUROC curve values of 0.92 (95% confidence interval [CI], 0.82–1.02), 0.78 (95% CI, 0.70–0.86), and 0.80 (95% CI, 0.76–0.84), respectively. It identified patients in the CUHK study who developed HCC in 3, 5, and 10 years, with AUROC curve values of 0.85 (95% CI, 0.75–0.95), 0.82 (95% CI, 0.70–0.93), and 0.78 (95% CI, 0.70–0.870), respectively. When data on HBV DNA were removed from the REACH-B scoring system, it identified patients in the ERADICATE-B cohort who developed HCC in 3, 5, and 10 years, with AUROC curve values of 0.90 (95% CI, 0.81–1.0), 0.76 (95% CI, 0.68–0.85), and 0.78 (95% CI, 0.73–0.82), respectively. It identified patents in the CUHK cohort who developed HCC in 3, 5, and 10 years, with AUROC curve values of 0.84 (95% CI, 0.79–0.92), 0.81 (95% CI, 0.71–0.91), and 0.79 (95% CI, 0.72–0.87). These modified systems identified patients who developed HCC with similar levels of accuracy as the original REACH-B score (P > .05 in tests of noninferiority). Including data on serum level of HBsAg or removing data on level of HBV DNA do not alter the accuracy of the REACH-B scoring system in determining HCC risk in patients with chronic HBV infection without cirrhosis. It might be cost effective to replace the test for HBV DNA with assays to measure HBsAg in determining HCC risk. These modified scoring systems might replace the REACH-B system in specific situations.